Investigations Into Bioenergetic Neuroprotection of Cone Photoreceptors: Relevance to Retinitis Pigmentosa - Narayan, Daniel S.; Chidlow, Glyn; Wood, John P. M.; Casson, Robert J. (Frontiers in Neuroscience, 2019)
Recent studies suggest cone degeneration in retinitis pigmentosa (RP) may result from intracellular energy depletion. We tested the hypothesis that cones die when depleted of energy by examining the effect of two bioenergetic, nutraceutical agents on cone survival. The study had three specific aims: firstly, we, studied the neuroprotective efficacies of glucose and creatine in an in vitro model of RP. Next, we utilized a well-characterized mouse model of RP to examine whether surviving cones, devoid of their inner segments, continue to express genes vital for glucose, and creatine utilization. Finally, we analyzed the neuroprotective properties of glucose and creatine on cone photoreceptors in a mouse model of RP. Two different bioenergy-based therapies were tested in rd1 mice: repeated local delivery of glucose and systemic creatine. Optomotor responses were tested and cone density was quantified on retinal wholemounts. The results showed that glucose supplementation increased survival of cones in culture subjected to mitochondrial stress or oxidative insult. Despite losing their inner segments, surviving cones in the rd1 retina continued to express the various glycolytic enzymes. Following a single subconjunctival injection, the mean vitreous glucose concentration was significantly elevated at 1 and 8 h, but not at 16 h after injection; however, daily subconjunctival injection of glucose neither enhanced spatial visual performance nor slowed cone cell degeneration in rd1 mice relative to isotonic saline. Creatine dose-dependently increased survival of cones in culture subjected to mitochondrial dysfunction, but not to oxidative stress. Despite the loss of their mitochondrial-rich inner segments, cone somas and axonal terminals in the rd1 retina were strongly positive for both the mitochondrial and cytosolic forms of creatine kinase at each time point examined. Creatine-fed rd1 mice displayed enhanced optomotor responses compared to mice fed normal chow. Moreover, cone density was significantly greater in creatine-treated mice compared to controls. The overall results of this study provide tentative support for the hypothesis that creatine supplementation may delay secondary degeneration of cones in individuals with RP.